Accuracy of serological tests for COVID-19: A systematic review and meta-analysis - Zheng, Xiaoyan; Duan, Rui hua; Gong, Fen; Wei, Xiaojing; Dong, Yu; Chen, Rouhao; yue Liang, Ming; Tang, Chunzhi; Lu, Liming (Frontiers in Public Health, 2022)
OBJECTIVE To determine the diagnostic accuracy of serological tests for coronavirus disease-2019 (COVID-19). METHODS The primary outcomes included overall sensitivity and specificity, as stratified by the methods of serological testing (enzyme-linked immunosorbent assays [ELISAs], lateral flow immunoassays [LFIAs] or chemiluminescent immunoassays [CLIAs]) and immunoglobulin classes (IgG, IgM or both). Secondary outcomes were stratum-specific sensitivity and specificity within the subgroups, as defined by study or participant characteristics, which included the time from the onset of symptoms, testing via commercial kits or an in-house assay, antigen target, clinical setting, serological kit as the index test and the type of specimen for the RT–PCR reference test. RESULTS 8785 references were identified and 169 studies included. Overall, we judged the risk of bias to be high in 47.9 % (81/169) of the studies, and a low risk of applicability concerns was found in 100% (169/169) of the studies. For each method of testing, the pooled sensitivity of the ELISAs ranged from 81% to 82%, with sensitivities ranging from 69% to 70% for the LFIAs and 77% to 79% for the CLIAs. Among the evaluated tests, IgG (80% to 81%)-based tests exhibited better sensitivities than IgM-based tests (66% to 68%). IgG/IgM-based CLIA had the highest sensitivity (87% [86% to 88%]). All of the tests displayed high specificity (97% to 98%). Heterogeneity was observed in all of the analyses. The detection of nucleocapsid protein (77% to 80%) as the antigen target was found to offer higher sensitivity results than surface protein detection (66% to 68%). Sensitivity was higher in the in-house assays (78% to 79%) than in the commercial kits (47% to 48%). CONCLUSION Among the evaluated tests, ELISA and CLIA tests performed better in terms of sensitivity than did the LFIA. IgG-based tests had higher sensitivity than IgM-based tests, and combined IgG/IgM test-based CLIA tests had the best overall diagnostic test accuracy. The type of sample, serological kit and timing of use of the specific tests were associated with the diagnostic accuracy. Due to the limitations of the serological tests, other techniques should be quickly approved to provide guidance for the correct diagnosis of COVID19